Sleep–wake rhythm and its association with lifestyle, health-related quality of life and academic performance among Japanese nursing students: a cross-sectional study - Momoko Kayaba (BMC, 2021)
Abstract Background Young adults are likely to have activities and go to bed late at night due to their age-dependent delayed endogenous circadian clock. The purpose of the present study was to clarify sleep–wake rhythm and its association with lifestyle, health-related quality of life, and academic performance among nursing students. Methods Self-reported questionnaires were distributed to undergraduate nursing students at six universities in Japan. Sleep–wake rhythm was assessed using the morningness-eveningness questionnaire. A quantitative design using the generalized linear mixed effect model was utilized to identify the factors related to the evening type among female nursing students (n = 447). Results About 18% of the participants were identified as the evening type. Evening type was associated with living alone, part-time job, and club activity. Sleep duration on weekdays was shorter, meal time duration was the shortest, and the percentages of students who skipped meals and those who gained body weight were higher in the evening type than in the morning type and intermediate type. Mental health-related quality of life was lower in the intermediate type and evening type than in the morning type, while there was no difference in physical health-related quality of life among these groups. The percentages of the nursing students who have experienced absence, tardiness, falling asleep during class, and/or interference with academic achievement were higher in the evening type than in other groups. Conclusions The present study has important implications for nursing students’ biological characteristics and lifestyle, which are associated with their health-related quality of life and academic performance.